«COLLECTIVE RIGHTS» OF ETHNIC COMMUNITIES: EXAMINATION OF SOCIAL AND LEGAL CONCEPTS - M. A. Yuzhanin (Модернизация, инновация, развитие, 2016)
Attitude to so-called «collective rights» of ethnic groups as to a basis of ethno-national politics of every progressive state and of the whole global social community has lately become popular. Social and legal aspects of this notion are examined along with «pro» and «contra» its practicalimplementation. «Collective rights» notion allows at least five contradicting readings. Arguments for «ethno-group rights» are speculative and easily contested. If spread, «collective rights» of ethnic groups may essentially undermine system integration bases of multiethnic nations. Ethnosocialproblems that do exist in the world may be solved in democratic ways on the basis of already available and broadly accepted human and civil rights concepts and by applying «collective measurement» of individual rights.